A new polymorphic locus, D7S411, isolated by cloning from preparative pulse-field gels is close to the mutation causing cystic fibrosis. - Ramsay, M; Wainwright, B; Farrall, M; Estivill, X; Sutherland, H; Ho, M; Davies, R; Halford, S; Tata, F; Wicking, C (1990)
The mutation causing cystic fibrosis (CF) has been localized to the DNA sequence of 700 kb bounded by the loci identified by the markers pMP6d-9 (D7S399) and pJ3.11 (D7S8). A 560-kb fragment obtained after SacII digestion of DNA from a cell line containing this region of human chromosome 7 in a mouse background was separated using pulse-field gel electrophoresis and isolated from the gel. The DNA was digested with BamHI prior to cloning into lambda EMBL3. Approximately 0.1% of the resulting clones contained human repetitive sequences, and 24 such recombinants were studied. Of these, 23 are on chromosome 7; 8 clones were duplicated, and of the 15 different recombinants, 7 are between MET and INT1L1, and a further 7 are between INT1L1 and pMP6d-9, leaving a single marker, pG2, which is between pMP6d-9 and pJ3.11. pG2 recognizes an RFLP with XbaI. A cosmid walk from pG2 has generated a further marker, H80, which recognizes an RFLP with PstI. This new locus (D7S411) divides the remaining region between the CF flanking markers, thereby making it more accessible to fine pulse-field mapping and allowing the precise localization of further clones to this region. Although it is not possible to position the CF locus unequivocally with respect to D7S411, both polymorphic markers at this locus exhibit low but significant linkage disequilibrium with CF, placing the emphasis for the search for the gene on the D7S399 to D7S411 interval of 250 kb.